Reading the Visual Signs of “Young, Different and Dangerous” in Fashion Spread of NYLON Indonesia Magazine January 2012 - Felkiza Vinanda; Priska Febrinia Handoyo; Aylanda D. Nugroho (Kata Kita: Journal of Language, Literature, and Teaching, 2014)
This study aims at showing the visual signs used to signify the concept of “Young, Different and Dangerous” in a magazine’s fashion spread. The visual signs are observed by using Dyer’s theory of human signs (1982) and the analysis is focused on the reading of visual signs at two orders of signification, the denotation and connotation. The findings show that the model’s appearance, manner, activity and setting of place are reflections of the magazine’s desired concepts, which suggested by the editor-in-chief. By understanding this, the visual images in fashion magazine, especially NYLON Indonesia, are constructed in such a way to reflect the magazine’s identity and to communicate the magazine’s branding as well